Exploring the challenges of medical/nursing tasks in home care experienced by caregivers of older adults with dementia: An integrative review. Issue 23 (9th August 2019) - Lee, Mijung; Ryoo, Ji Hoon; Campbell, Cathy; Hollen, Patricia J.; Williams, Ishan C.
Abstract: Aims: To examine prevalence, types, challenges and the impact of medical/nursing tasks (MNT) on caregivers of older adults with dementia. Background: Medical/nursing tasks have been perceived as a professional healthcare role; however, research shows that many caregivers of older adults with dementia perform those tasks in the home, such as giving injections, tube feedings or operation of medical equipment. Little is known about the caregivers' challenges in engaging in these MNT. Design: Integrative review. Methods: Ovid MEDLINE, CINAHL, PsycINFO and Web of Science databases were searched to explore MNT among caregivers of older adults with dementia who lived in a community setting. Four quantitative and nine qualitative studies published between 1980–2018 were included. Overall, process of the review was guided by PRISMA. Results: About 67% of U.S. caregivers of older adults with dementia performed MNT, including managing multiple medications, wound care and nutritional management. Care recipients' cognitive impairment complicated the provision of those tasks due to their limited cognitive functioning, behavioural changes, comorbidities and complex medication regimen. Insufficient information and training from healthcare professionals as well as caregivers' age and their own health problems made performance of those tasks even more challenging. As a result, caregivers frequently suffered from emotional distress such as worrying, anxiety and sleep disturbance. Conclusions: Medical/nursing tasks have become one of the daily tasks of caregivers of older adults with dementia within the home. However, the tasks are difficult and complicated, and inadequate support from healthcare professionals may compromise the caregivers' well‐being. Relevance to clinical practice: Healthcare professionals should provide education and should be aware of caregivers' needs related to MNT. Structured‐medical information, skill‐based instructions and hands‐on training may be beneficial to decrease the caregivers' distress from MNT.